Study Analysis Fuel from Plastic Waste - Azharuddin; Dwi Arnoldi; Fenoria Putri; Kemas M. Fadhil Almakky; M. Ivan Davala (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
The explosion of plastic-based waste (polymer) in the environment, as a result of its excessive use, so that this phenomenon causes damage to environmental ecosystems, water absorption is not optimal causes flooding, and polluting nutrients in the soil. Plastic is a polymer compound composed of the main elements, namely carbon and hydrogen. The best results in this study by using this tool have a physical appearance: yellow like premium fuel type "1.0" (color test results using the ASTM D1500 method), very pungent smelling liquid, thicker when compared to premium fuel types. And has specifications: Density value of 786.4 kg/m3, Sulfur Content 0.003% m/m, water content 282 ppm, CCI 53.4.